Afghanistan local government system: a comparative analysis - Enayatzade, Shakila (My University, 2018)
Bu Afganistan'ın yerel yönetim sistemi hakkındadır ve Afganistan’ın idari yapısına odaklanmaktadır. Afganistan’ın yerel yönetim yapısı, 2001 sonrası yerel yönetim sisteminin yavaş gelişmesinin nedenlerini daha iyi değerlendirilebilmek amacıyla Türkiye'nin yerel yönetim sistemi ile karşılaştırılmıştır. Afganistan’ın yerel yönetim sistemini güçlendirmek adına uluslararası düzeyde milyonlarca dolar harcanmasına rağmen sistem hala zorluklarla karşı karşıya kalmaktadır. Ademi merkezileşme aynı zamanda hizmetlerin yerel topluma nasıl sağlandığını ve ülkenin demokratik sisteme sahip olup olmadığını da işaret etmektedir. Çalışmanın Birinci Bölümünde, addemi merkezileşmenin tanımı üzerinde durularak İngiltere ve ABD örnekleri açıklanacaktır. İkinci bölümde, Türkiye’deki yerel yönetimler, yerel yönetimlerin tabi olduğu mevzuat ve yerel yönetimlerin yetki ve sorumlulukları incelenecektir. Üçüncü bölümde ise Afganistan'ın yerel yönetim sistemi, yerel yönetimlerin yetki ve sorumlulukları ve yerel yönetim politikaları ele alınacaktır. Son bölümde ise Türkiye ve Afganistan’ın yerel yönetim sistemleri karşılaştırmalı bir şekilde incelenecektir ve tez, vurgulanan noktalar, metodoloji ve bulgular ile sonuçlandırılacaktır.

This thesis is about the local government system of Afghanistan, specifically concentrating on the administrative structures. It is compared with the local government system of Turkey in order to have a better assessment of the reasons behind the slow and insufficient improvements of the local government system after 2001. Although the local government system of Afghanistan has the primary attention and been the main target of the international community’s spending in the millions of dollars to strengthen the local government system and to foster good governance, it still faces challenges. Decentralization concentrates on how the services are provided to the locals and whether the country has a democratic system. In this thesis, the first chapter is about decentralization and the concept of government with two examples of England and US. The second chapter deals with the local government system of Turkey from administrative aspects, organs, legislations, and roles and responsibilities. The third one analyzes the local government system in Afghanistan, its type, responsibilities, authority, legislations and policies on local government. Moreover, the last chapter is concluded with findings from the comparison analysis study of both local government system, with highlighted points.
Keywords: 2001-; ademi merkezileşme; administrative structure; Afganistan; Afghanistan; authority; Central-local government relations; decentralization; idari yapısı; legislations; Local government; Merkez-yerel yönetim ilişkileri; mevzuat; Politics and government; Siyaset ve yönetim; Turkey; Turkiye local government; Yerel yönetim; yetki